Hepatitis E Virüs (HEV) Seropositivity in Blood Donors: The Efect of Some Demographic Characteristics on HEV Seroprevalence (Annals of Medical Research, 2021)
None
Keywords: Hepatitis E Virus, Seroprevalence, Enzyme-immunoassay, Blood Donors.